A blinded, randomized clinical trial evaluating the efficacy and safety of lokivetmab compared to ciclosporin in client‐owned dogs with atopic dermatitis. Issue 6 (14th September 2017) - Moyaert, Hilde; Van Brussel, Leen; Borowski, Stasia; Escalada, Monica; Mahabir, Sean P.; Walters, Rodney R.; Stegemann, Michael R.
Abstract : Background: Lokivetmab is an injectable anti‐canine‐IL‐31 monoclonal antibody to treat clinical manifestations of atopic dermatitis (AD) in dogs. Hypothesis/Objectives: To characterize the efficacy and safety of lokivetmab, and to demonstrate its noninferiority to ciclosporin under field conditions. Animals: Dogs with chronic AD ( n = 274) were enrolled from 40 practices in Belgium, The Netherlands, France and Germany. Methods: Animals were randomized (1:1) to oral ciclosporin (5 mg/kg/once daily) or monthly injectable lokivetmab (1–3.3 mg/kg) for three months. Eighty one animals that successfully completed the comparative phase were enrolled in a continuation phase receiving lokivetmab for an additional six months. Owners assessed pruritus on a Visual Analog Scale, skin lesions were assessed by veterinary investigators with a Canine AD Extent and Severity Index (CADESI‐03) scale. Results: Lokivetmab was noninferior to ciclosporin for pruritus reduction on Day 28 (51.90% versus 43.72%). For Day 28 CADESI‐03 percentage reduction, noninferiority of lokivetmab (54.17) versus ciclosporin (56.86%) was not achieved. At none of the time points were mean CADESI‐03 scores significantly different between groups. Continued efficacy towards pruritus and lesions was demonstrated in the continuation phase where 76.3% of animals ( n = 45) were assessed as 'normal' for pruritus at study end. No abnormal health events associated with lokivetmab were observed during the initial three month phase (142 dogs) or during the subsequent six month phase (81 dogs). Conclusions and clinical importance: Lokivetmab at a minimum monthly dose of 1 mg/kg provided quick onset (within one day) of a lasting effect in reducing pruritus and skin lesions with a good safety profile. Abstract : Background –Lokivetmab is an injectable anti‐canine‐IL‐31 monoclonal antibody to treat clinical manifestations of atopic dermatitis (AD) in dogs.Hypothesis/Objectives –To characterize the efficacy and safety of lokivetmab, and to demonstrate its noninferiority to ciclosporin under field conditions.Conclusions and clinical importance –Lokivetmab at a minimum monthly dose of 1 mg/kg provided quick onset (within one day) of a lasting effect in reducing pruritus and skin lesions with a good safety profile.